POTENSI PENGHEMATAN ENERGI KOMPRESOR MELALUI REPLACEMENT KOMPRESOR MENUJU TYPE AF OPC 55-10 - Putu Oka Sutrisna; Gusti Putu Suryawan (Lembaga Penelitian dan Pengabdian Masyarakat (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2022)
Compressors and compressed air systems are important areas for improving energy efficiency in industrial plants. The compressor engine is one of the machines that are included in the top 5 machines with the highest energy consumption. Based on the results of the analysis, the old compressor with a capacity of 90 KW only had a load of 70%, so another 30% wasted energy during the unload condition. The compressor engine which previously used high enough energy was replaced with a compressor engine type AF OPC 55-10 which uses more energy efficiently than the previous type because its capacity is only 55 KW. Through the use of this compressor, the compressor load can reach 90% and is more efficient in energy use. Thus, the potential for energy savings from the utilization of the compressor engine, reaches 306,600 kwh/year. or a potential cost savings of Rp. 442,945,020 per year. With a temperature of 50oC when operating (load) the motor output power is 193 KW and when not operating (unloaded) at a temperature of 45oC the motor output power is 186 KW from the nameplate data of 200 KW. The percentage of leaks in the compressed air system on the blow molding machine is > 10%.